Driving future sounds: imagination, identity and safety in electric vehicle noise design. Issue 1 (2nd January 2018) - Clendinning, Elizabeth A.
Abstract: Global soundscapes in the 20th century have largely been defined by the sounds of combustion-engine automobiles. Yet, as nearly-silent hybrid and electric vehicles (EVs) rise in popularity, newly created noises for such vehicles are necessary to ensure pedestrian safety. This article examines oft-competing aesthetic and practical concepts in electric vehicle sound design in dialog with Bourdieu's concept of cultural capital. First contextualizing the car and its noises as cultural capital within the 20th century, the articles demonstrates how concerns about noise pollution, safety, branding, and aesthetic opinions of what a futuristic car 'should' sound like–different ways vehicle noise functions within a soundscape–govern the sound design process. The Nissan Leaf, Toyota Prius, the Audi e-tron are presented as examples. The article also interrogates the perceived need for vehicle safety noise at all. Through focusing on the sonic imagination as embodied in the design process for electric vehicles, the article advocates for further discourse about how future vehicle noise design will shape soundscapes.